2015
DOI: 10.1039/c5gc00822k
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable thermoplastic elastomers derived from plant oil and their “click-coupling” via TAD chemistry

Abstract: We report the preparation of plant oil based triblock copolymers as thermoplastic elastomers with the aid of TAD chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 64 publications
2
62
0
Order By: Relevance
“…Elastic behavior of these SMPs was evaluated by step cyclic tensile tests that were performed at cyclic stretching deformation with a maximum strain of 50, 100, 150, 200, 250, 300, 350, and 400%. Similar to early reports on the cellulose graft copolymers, all these SMPs exhibited elastomeric behavior. As shown in Figure (a,b), it can be clearly seen that the elastic recovery values of EC‐ g ‐(PLMA‐ b ‐P(LMA‐ co ‐THFMA700)) and EC‐ g ‐P(LMA‐ co ‐THFMA700) increased with the increasing of the maximum strain in each step.…”
Section: Resultssupporting
confidence: 87%
“…Elastic behavior of these SMPs was evaluated by step cyclic tensile tests that were performed at cyclic stretching deformation with a maximum strain of 50, 100, 150, 200, 250, 300, 350, and 400%. Similar to early reports on the cellulose graft copolymers, all these SMPs exhibited elastomeric behavior. As shown in Figure (a,b), it can be clearly seen that the elastic recovery values of EC‐ g ‐(PLMA‐ b ‐P(LMA‐ co ‐THFMA700)) and EC‐ g ‐P(LMA‐ co ‐THFMA700) increased with the increasing of the maximum strain in each step.…”
Section: Resultssupporting
confidence: 87%
“…In recent years TAD-(di)ene click reactions were found very useful in the preparation of nanoparticles, 25 polymer bioconjugates synthesis of block co-polymers, 26 functionalization of polymers and materials etc. [27][28][29][30][31][32] In an earlier report, while demonstrating the rst example for the application of 'triazolinedione-ene' reactions to prepare nanoparticles, we have shown that this chemistry can be a useful platform to prepare spherical nanoparticles from multi-ene systems, such as plant oils, via a nanoprecipitation technique. 25 However, such methods cannot be applied for the preparation of asymmetric structures such as Janus particles.…”
Section: Introductionmentioning
confidence: 88%
“…Ganewatta et al . prepared thermoplastic elastomers from natural rosin and modified vegetable oil, and discussed other sustainable elastomers from renewable biomass . Plant based phenolic acids with varying functionalities were utilized to prepare thiol‐ene elastomers using a photoinitiator …”
Section: Sustainable Rubbers and Rubber Like Materialsmentioning
confidence: 99%